Vision. (K. Brown, Crown Point Press : Oakland, California, 1975)
The art journal published in Oakland in the 1970's. Curated by Tom Marioni of the Museum of Conceptual Art (MOCA) in San Francisco, this publication featured writing and images by a range of visual artists. Featured artists include Vito Acconci, Chris Burden, Brice Marden, and John Cage.; Geography, often a theme, plays a significant role in the content.